Modelling Machado-Joseph disease: from induced pluripotent Stem Cells to mature neuronal subtypes - Ramos, Cristiana Videira (2018)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia